Odpowiedzi

2010-04-17T22:52:48+02:00
X-pierwsza liczba
x-1/2-druga liczba
10x-trzecia liczba
x+(x-1/2)+10x=9 1/2
x+x-1/2+10x=9 1/2
x+x+10x=9 1/2+1/2
12x=10//:12
x=5/6
y+1/3+5/6=9 1/2
y=19/2-1/3-5/6
y=57/6-2/6-5/6
y=50/6
50/6=8 1/3
odp.1/3;5/6 i 8 1/3
2 5 2
2010-04-17T23:00:33+02:00
X+ x-1/2 + 10x= 9 1/2
12x- 1/2=9 1/2
12x= 9 1/2 +1/2
12x = 10 / :12
x=5/6
x-1/2=1/3
10x= 8 1/3
odp. 1/3, 5/6 i 8 1/3
2010-04-17T23:25:01+02:00
X-pierwsza liczba
x-½ - druga liczba = 2/6=1/3
10x - trzecia liczba = 50/6 = 25/3= 8⅓
9½=x+x-½+10x
9½+½=12x
10=12x
x=10/12=⅚
x= ⅚
x-½ = 2/6=⅓
10x = 50/6 = 25/3= 8⅓